PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DALAM ISLAM (STUDI PADA PT BOSOWA BERLIAN MOTOR KOTA PALOPO) - .... ...... (Program Studi Perbankan Syariah, IAIN Palopo, 2020)
Abstract: In this study the formulation of the problem is is there an influence of work motivation on performanceemployees in Islam, simultaneously and partially on the performance of employees at PT. Bosowa Berlian Motor Palopo City. The hypothesis proposed there is the effect of work motivation simultaneously and partially on employee performance at PT. Bosowa Berlian Motor Palopo City. This study aims to determine the effect of work motivation on employee performance at PT Bosowa Berlian Motor. This study uses a direct survey method to the company by going directly to the field accompanied by distributing questionnaires that have been prepared. And the analytical method used in this study is simple regression analysis. The sampling technique used is saturated sampling technique, which is the technique of determining the sample when all members of the population are used samples. this is often done if the population is relatively small, less than 30 (thirty) people. The population used is 26 employees. Based on the results of this study motivation has a significant effect on employee performance at PT Bosowa Berlian Motor, indicated by a significant value of p = 0.012 less than α = 0.05 (0.012 <0.05) with a regression coefficient amounted to 0.490. In connection with the results of hypothesis testing, the results of this study indicate the influence of work motivation and work ability both simultaneously and partially. The influence arising from the results of the study shows a positive direction, which means that better work motivation and good work skills will improve employee performance. Motivation to work in Islam solely expects the blessing of Allah SWT, by giving thanks, giving thanks for the blessings that have been given, and doing pious practices, Motivation works to get pious practices in the world. working in Islam is only pursuing